Tool-Based Requirement Traceability between Requirement and Design Artifacts - Turban, Bernhard (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2013)
Processes for developing safety-critical systems impose special demands on ensuring requirements traceability. Achieving valuable traceability information, however, is especially difficult concerning the transition from requirements to design. Bernhard Turban analyzes systems and software engineering theories cross-cutting the issue (embedded systems development, systems engineering, software engineering, requirements engineering and management, design theory and processes for safety-critical systems). As a solution, the author proposes a new tool approach to support designers in their thinking in order to achieve traceability as a by-product to normal design activities and to extend traceability information with information about design decision rationale.   Contents ·         Requirement Engineering and Management ·         Design Theories ·         Quality Standards for Safety-Critical Development Processes ·         Rationale Management ·         Requirement Traceability ·         A Tool Approach for Requirement Traceability between Requirements and Design     Target Groups ·         Researchers and students in the fields of requirement traceability, design theory, rationale management, development of safety-critical systems ·         Engineers in the fields of requirements engineering, systems engineering, and software engineering of safety-critical systems   Author Dr. Bernhard Turban completed his doctoral degree at the Institute for Information and Media, Language and Culture of the University of Regensburg under the supervision of Prof. Dr. Christian Wolff. He is an advisor in the fields of processes and tools for requirements engineering.